Event‐triggered fault estimation for discrete time‐varying systems subject to sector‐bounded nonlinearity: A Krein space based approach - Li, Yueyang; Liu, Shuai; Zhao, Dong; Shi, Xiaorui; Cui, Yigang (International journal of robust and nonlinear control, 2021)
In this study, event‐triggered fault estimation (FE) problem for a class of discrete‐time dynamic systems subject to sector‐bounded nonlinearity and time‐varying coefficients is investigated. For a given event‐triggered measurement transmission scheme, the event‐induced output non‐persistence for the fault estimator is modeled by norm‐bounded observation uncertainty. After giving a suitable H∞ performance index and formulating the estimation problem for the concerned nonlinear system with event‐triggered measurements, an auxiliary model in a quasi‐linear form and an associated H∞ performance function are established. With the aid of this auxiliary model and performance function, the sector‐bounded nonlinearity condition and the induced observation uncertainty are packaged simultaneously, and the considered H∞ FE problem in Hilbert space is recast as an H2 deconvolution filtering issue in Krein space. Through designing Krein space based model with appropriate inner products, and using the orthogonally projection technique, fault estimator is derived in an analytical and recursive manner. The condition that ensures the existence of the estimator is also obtained. Two examples are adopted to demonstrate the applicability of the proposed method.